Resisting hate crime discourse: queer and intersectional challenges to neoliberal hate crime laws - Meyer, Doug (Critical criminology, 2014)
Hate crime laws have reinforced neoliberalism by expanding police and prosecutorial power, adding to the rapid expansion of incarcerated populations. Further, hate crime discourse associates anti-queer violence with notions of "stranger danger," and thereby reproduces problematic race and social class politics in which an innocent, implicitly middle-class, person is suddenly and randomly attacked by a hateful, implicitly low-income, person. Thus, the author argues that queer and intersectional resistance should reject hate crime discourse and, instead, focus on the experiences of marginalized lesbian, gay, bisexual, and transgender (LGBT) people. By doing so, scholarship and activism concerned with reducing anti-queer violence can benefit a wide range of LGBT people without reinforcing inequalities based on race and social class.